1998
DOI: 10.1159/000012287
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the French Translation of the Agoraphobic Cognitions Questionnaire

Abstract: Background: The goal of the present study was to validate the French version of the Agoraphobic Cognitions Questionnaire (ACQ). Methods: Subjects consisted of 115 patients with panic disorder and agoraphobia, 54 obsessive-compulsive patients and 72 normal controls. Patients were referred for outpatient treatment. They filled in the questionnaire before and after entering treatment. The control group consisted of people taken from the general population. It was matched with the clinical groups on age, sex and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…Given that this large proportion of variance was parceled out prior to testing the predictive value of the postacute treatment cognitive variables, it is easy to understand why social catastrophe cognitions did not emerge as a significant predictor. Prior research (e.g., Bouvard et al, 1998;Chambless & Gracely, 1989) has indicated that thoughts of physical catastrophes are the only type of cognitions capable of discriminating panic disorder from other anxiety disorders. This implies that physical catastrophe cognitions are more central to the development of panic disorder as distinguished from other anxiety disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Given that this large proportion of variance was parceled out prior to testing the predictive value of the postacute treatment cognitive variables, it is easy to understand why social catastrophe cognitions did not emerge as a significant predictor. Prior research (e.g., Bouvard et al, 1998;Chambless & Gracely, 1989) has indicated that thoughts of physical catastrophes are the only type of cognitions capable of discriminating panic disorder from other anxiety disorders. This implies that physical catastrophe cognitions are more central to the development of panic disorder as distinguished from other anxiety disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In previous analyses of agoraphobics' responses to the ACQ alone, a loss of control factor has emerged [Arrindell, 1993a;Bouvard et al, 1998;Chambless et al, 1984]. When agoraphobic patients' data on the combined items of the ACQ and BSQ in the present study are examined, loss of control again emerges as a coherent factor, with the addition of the fear of disorientation item from the BSQ.…”
Section: Latent Structure Of Fear Of Fearmentioning
confidence: 60%
“…In prior research on the Agoraphobic Cognitions Questionnaire, Chambless et al [1984] demonstrated two clear factors: thoughts about impending loss of control and thoughts about physical malady resulting from anxiety. Arrindell [1993a] and Bouvard et al [1998] have replicated these findings. In a factor analysis of a different measure, the Agoraphobic Cognitions Scale, Hoffart et al [1992] obtained three factors.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…The internal consistency was good for BAI‐Malay (α = .91) (Mukhtar & Zulkefly, ), PAS (α = .86) (Bandelow, ), FQ (α = range .71–.86) (Lee & Oei, ; Oei, Moylan, & Evans, ), and ACQ (α = .80) (Chambless et al, ). All measures were found to have an acceptable concurrent validity (Bandelow, ; Marks & Mathews, ; Mukhtar & Zulkefly, ) and discriminant validity (Bandelow et al, ; Bouvard et al, ; Marks & Mathews, ; Oei et al, ).…”
Section: Methodsmentioning
confidence: 98%